Photobook Siti Kewe The Highland Of Gayo - Muhammad Irfan Nugraha Kamil Abdullah (Pascasarjana ISBI Bandung, 2019)
The producint of ethno-graphy photobook of Siti Kewe: The Highland of Gayo is the representation of life cycle of coffee seed and the struggle of arabica coffee farmers in Gayo Highland. Coffee has become a significant part in the life of Gayo tribe in Middle Aceh. Moreover, it also becomes the way Gayo peole live. Gayo coffee has become the identity of the Gayo tribe. The photobook is produced through the ethnographic approach involving the artist or the photographer who is also the part of the subject’s life. The photobook is designed into a 20 x 25cm book with colorful paper to show the elegance. The ethnography photobook Siti Kewe: The Highland of Gayo becomes the narrative and visual medium in documenting the tradition of Gayo people in Middle Aceh in their behavior toward arabica coffee and their understanding values toward the viewpoint of Gayo people. The culture documentation may bridge the future generation not to loss values. Keywords: ethno-photography, photobook, Gayo coffee